Statistics and probability - Belecina, Rene R.; Baccay, Elisa S.; Mateo, Efren B. (Quezon City : Rex Book Store, 2016)
Statistic and probability is a worktext aligned to the K-12 Curriculum of the Department of Education, Lessons are organized using spiral approach, assuring that there are no gaps and overlaps from the Grade 10 curriculum and the higher education GEC math subjects. The Lesson structure adopts the Readiness-Engagement-Mastery (R-E-M) model of Rex Book Store, Inc.
Includes index.
English text.
Keywords: Probabilities and applied mathematics; Statistical mathematics